2022
DOI: 10.1101/2022.07.01.498342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network of hotspot interactions cluster tau amyloid folds

Abstract: Cryogenic electron microscopy has revealed unprecedented molecular insight into the conformation of β-sheet-rich protein amyloids linked to neurodegenerative diseases. It remains unknown how a protein can adopt a diversity of folds and form multiple distinct fibrillar structures. Here we develop an in silico alanine scan method to estimate the relative energetic contribution of each amino acid in an amyloid assembly. We apply our method to twenty-seven ex vivo and in vitro fibril structural polymorphs of the m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 63 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…We next interpreted the putative stability of these interactions. We leveraged a recently described computational method that captures the energetic contribution of interactions in a fibril based on changes in calculated energy of the assembly following alanine substitution 42 . Application of this method allows us to begin interpreting which interactions are important in our fibril assembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next interpreted the putative stability of these interactions. We leveraged a recently described computational method that captures the energetic contribution of interactions in a fibril based on changes in calculated energy of the assembly following alanine substitution 42 . Application of this method allows us to begin interpreting which interactions are important in our fibril assembly.…”
Section: Resultsmentioning
confidence: 99%
“…While our understanding of how these different fibrillar shapes are formed remains unknown, more general rules have emerged. We have found that the core amyloid motif interactions are modular in the ex vivo structures followed by more peripheral secondary interactions 42 . In the present work, we demonstrate a new way dysregulate local structures and promote amyloid motif exposure using lysine acetylation, which promotes gain-of-function interactions.…”
Section: Design Of Tau Elements To Regulate Tau Aggregationmentioning
confidence: 87%
See 1 more Smart Citation
“…We employed the Rosetta design module to computationally engineer the tau sequence using the CBD and PiD cryo-EM structures as templates (see methods) 33 . For the CBD fibril conformation, we optimized the 320 and 328 positions allowing sampling of all possible amino acid combinations yielding a matrix of 400 designed mutants.…”
Section: Computational Design Of Nonpolar Contacts Produces Spontaneo...mentioning
confidence: 99%
“…Changes in assembly energy were calculated using a method adapted from the Flex ddG protocol described by Barlow et. al 49 and more recently expanded for cryo-EM fibril assemblies 33 . From the input assembly, a set of pairwise atom constraints with a maximum distance of 9 Ang are generated with a weight of 1, using the fa_talaris2014 score function.…”
Section: Computational Design Of Tau Sequences Using Fibril Backbones...mentioning
confidence: 99%